Differences between Belgian and Brazilian group A Streptococcus epidemiologic landscape - Smeesters, Pierre Robert (2006)
Background. Group A Streptococcus (GAS) clinical and molecular epidemiology varies with location and time. These differences are not or are poorly understood. Methods and Findings. We prospectively studied the epidemiology of GAS infections among children in outpatient hospital clinics in Brussels (Belgium) and Brası´lia (Brazil). Clinical questionnaires were filled out and microbiological sampling was performed. GAS isolates were emm-typed according to the Center for Disease Control protocol. emm pattern was predicted for each isolate. 334 GAS isolates were recovered from 706 children. Skin infections were frequent in Brası´lia (48% of the GAS infections), whereas pharyngitis were predominant (88%) in Brussels. The mean age of children with GAS pharyngitis in Brussels was lower than in Brası´lia (65/92 months, p,0.001). emm-typing revealed striking differences between Brazilian and Belgian GAS isolates. While 20 distinct emm-types were identified among 200 Belgian isolates, 48 were found among 128 Brazilian isolates. Belgian isolates belong mainly to emm pattern A–C (55%) and E (42.5%) while emm pattern E (51.5%) and D (36%) were predominant in Brası´lia. In Brası´lia, emm pattern D isolates were recovered from 18.5% of the pharyngitis, although this emm pattern is supposed to have a skin tropism. By contrast, A–C pattern isolates were unfrequently recovered in a region where rheumatic fever is still highly prevalent. Conclusions. Epidemiologic features of GAS from a pediatric population were very different in an industrialised country and a low incomes region, not only in term of clinical presentation, but also in terms of genetic diversity and distribution of emm patterns. These differences should be taken into account for designing treatment guidelines and vaccine strategies.